Improvement of Management Accounting in Uzbekistan: Problems, Integration and Development Prospects (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article discusses modern approaches to management accounting in Uzbekistan, including the stages of its development, integration with financial accounting and the impact of digitalization on the accounting system. The author analyzes the main problems of implementing management accounting, such as a shortage of qualified specialists, a lack of a methodological base and the need to adapt to international financial reporting standards (IFRS). The article offers recommendations for improving management accounting, including the creation of a national certification system, the introduction of automated technologies and the development of a flexible accounting policy focused on the internal needs of companies. It is concluded that the development of management accounting is strategically important for increasing the competitiveness of Uzbek enterprises and strengthening their position in the international market.